Clinical and radiological comparison of the application of bone plates on the lateral and dorsal side of the os ilium in the treatment of corpus ossis ilium fractures in cats - Nuriza Zamirbekova; Elgin Orçum Uzunlu; Birol Özdil; Mustafa Arıcan (Eurasian Journal of Veterinary Sciences)
Aim: In the present study, it was aimed to evaluate the clinical and radiological results in the post-operative period by placing LC-DCP or reconstruction plates on the dorsal and lateral of the fracture line in cases of corpus ossis ilium fractures in cats. Materials and Methods: The study material consist 14 cats with different breed, gender and age. Plate osteosynthesis was applied to the dorsal of the corpus ossis ilium in 7 cats with an ilium fracture, and laterally to the other 7 cats. In total, a 1.5 mm reconstruction plate was used in 8 cases, and a 1.5 and 2.0 mm LC-DCP plate was used in 6 cases. A locked lack screw of 2.0/16 mm and 2.0/14 mm was used in 2 cases with sacroiliac luxation. Results: Lateral application was easy when the fracture line was in the cranial part of the corpus ossis ilium. Dorsal application was more difficult due to the anatomical structure of the os ilium. During the study, preoperative hemothorax in 3 cases, pnömothorax and lung contusion in 1 case, constipation in 4 of 14 cases, urinary bladder problem in 4 cases, numbness and paraplegia in the tail in 3 cases were observed postoperatively. Conclusion: As a result, no difference was observed between the post-operative clinical and radiological results of placing LC-DCP or reconstruction plates on the dorsal and lateral of the bone. Because of the locked plate and screws kept the fracture fragments more rigid, no screw loosening was observed in both methods.